CRITERIOS PARA EL MANEJO Y PROTECCIÓN DE ESPECIES FORESTALES MADERABLES CRÍTICAS DEL NOROCCIDENTE DEL ECUADOR - Palacios, Walter (2009)
The Ecuador’s west north is the zone of major wood’s production of the country. Due to this situation, the populations of several species of trees that have commercial value are severely affected. A characteristic of the tropical Ecuadorian forests is the great wealth of their flowers, though with a poor wealth of the production of wood. The tropical humid forests on firm land of Emeralds lived in this reality. In this place, few species can offer advantages for their utilization, such it is the case of the sande Brosimum utile, which reaches among 40 and 80% of usable volume for the trees bigger than 60 DAP’s cm (Palacios & Jaramillo, 2001) with an average of 60 m3 for hectare. Inside the slightly abundant species and high commercial value are species like the chanul Humiriastrum procerum, and the sleepy-head Cojoba arbórea. These and other results were achieved by means of a series of forest inventories applied to all the trees bigger than 10 DAP’s cm, in six communities of the north of Emeralds, in the West north of Ecuador. Among the information that it was taken: the species, the diameter and the number of trees for species. 110 Palacios & Jaramillo: Manejo, especies forestales The results of the inventories allowed to know between other aspects the abundance of the species, one of the parameters key to programmer the utilization of the forest, or to determine its protection